2018
DOI: 10.1155/2018/7841026
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Emergency Healthcare System for Elderly Community in Outdoor Environment

Abstract: By exploiting the advanced information and communication technologies, the current community healthcare systems provide digital healthcare services. However, the current healthcare framework for senior citizen in outdoor environment faces new challenges. The traditional healthcare systems are not efficient, and they do not comprise user-friendly devices and interfaces suitable for the elderly in outdoor environment. Hence, in this work, we develop an outdoor healthcare system for community senior citizens base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Research has shown that drones can enhance the delivery and access to health care for patients who would be restricted from adequate services due to cost, location, or infrastructure Copyright © Tina M Penhollow AJHS.000504. 1(1).2019 [9,10]. The application of drones in health emergency situations around the world appears to be a promising and useful tool.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that drones can enhance the delivery and access to health care for patients who would be restricted from adequate services due to cost, location, or infrastructure Copyright © Tina M Penhollow AJHS.000504. 1(1).2019 [9,10]. The application of drones in health emergency situations around the world appears to be a promising and useful tool.…”
Section: Discussionmentioning
confidence: 99%
“…These technologies have been used for various medical purposes, particularly in monitoring the health of the elderly. This way, data can be collected on general health and dangerous situations by capturing important vital signs [ 15 ].…”
Section: Iot-based Healthcare Systems and Their Applicationsmentioning
confidence: 99%
“…According to findings from the Global Burden Disease Study carried out in 2013, global health is continuously improving over the years indicating improvements in healthcare services provided [5]. Several countries have adapted UHC mechanism in which free services have been provided by the government for all-age groups.…”
Section: Background Overviewmentioning
confidence: 99%